Treatment of Newborns and Infants in Japan suffering from Pneumonia with New Antibiotics - Susumu Nakazawa (Paediatrica Indonesiana, 1975)
Despite the recent development of a high state of chemotherapy in Japan, there has not necessarily been an improvement in the prognosis of pneumonia in infants and newborns. Upon bacteriological examination, relevant causative organisms such as pathogenic staphylococci, pneumococci, streptococci, and gram-negative bacteria have been detected as causing mixed infection. Suitable chemotherapeutic agents which diffuse well to the lung and show high bactericidal action against such organisms must be selected to combat the infection. A combination of two synthetic penicillins, ampicillin, effective against gram-negative as well as gram-positive bacteria and cloxacillin effective against resistant staphylococci, was used for the treatment of many cases of pneumonia in infants and newborns and satisfactory results were obtained. The results of this study and an appraisal of penicillin combination therapy will be discussed.